Implementation of the Reading Corner Program to Increase Children's Interest in Reading in Arjasari Village - Kusnadi, Edi; Maharani, Fadhilla Zahra; Tasdiah, Shofa; Aisyah, Miranda; Akbar, Dede Yopi; K, Arya Restu; Hidayat, Taufik; Fauzan, M Rifal; Rosita, Imas; Nabila, Widya Ainatun; Salsabila, Salsabila; Wulandari, Ema (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The reading corner program in Arjasari Village aims to increase people's interest in reading. This research identified various challenges faced in implementing the program, such as limited resources, lack of interest in early reading in the community, and lack of variety of reading books. The reading corner program not only increases people's interest in reading, but also has a positive impact on other social aspects, such as increasing knowledge, communication skills and a sense of togetherness. Apart from that, this program also contributes to the development of a more advanced and cultured society. This research highlights the importance of literacy programs as an effort to empower society. Through a participatory approach, various solutions have been implemented to overcome these challenges, such as collaborating with regional libraries, involving community leaders, and holding sustainable literacy activities. This research concludes that with the right strategy, the reading corner program can be an effective solution for increasing literacy in rural areas.